2008
DOI: 10.1021/jf073073b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, in Vitro Fermentation Characteristics, and in Vivo Digestibility Responses by Dogs to Select Corn Fibers

Abstract: The objective was to examine the chemical composition, in vitro fermentation characteristics, and in vivo digestibility responses of fiber-rich corn coproducts resulting from corn wet milling. Native corn fibers, native corn fibers with fines, hydrolyzed corn fibers, and hydrolyzed extracted corn fibers were analyzed chemically and their capacity to produce short-chain fatty acids determined. Ash content was low (<1.2%), crude protein content varied little, but fat and fiber concentrations varied widely. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…However, in this case, the authors observed a higher percentage of DM in the faeces. As to corn fibre, as in the present study, GUEVARA et al (2008) reported no differences in the weight of faeces from dogs that received a diet supplemented with this ingredient compared to animals fed with control diet. However, the moisture content of faeces from animals fed with corn fibre was less than that in the other animals' faeces, unlike what was observed in the present study, in which the median moisture content (66.3%) was slightly higher in the faeces, resulting in a faecal score below the desired value (score 3 according to de-OLIVEIRA et al, 2008).…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…However, in this case, the authors observed a higher percentage of DM in the faeces. As to corn fibre, as in the present study, GUEVARA et al (2008) reported no differences in the weight of faeces from dogs that received a diet supplemented with this ingredient compared to animals fed with control diet. However, the moisture content of faeces from animals fed with corn fibre was less than that in the other animals' faeces, unlike what was observed in the present study, in which the median moisture content (66.3%) was slightly higher in the faeces, resulting in a faecal score below the desired value (score 3 according to de-OLIVEIRA et al, 2008).…”
Section: Resultssupporting
confidence: 47%
“…FISCHER et al (2012) observed a higher faecal concentration of propionate in cats fed with a diet supplemented with wheat bran (140.53mmol kg -1 DM) compared to animals fed with the control diet (without fibre supplementation) (72.93mmol/kg DM), confirming that this ingredient undergoes a certain degree of fermentation. Furthermore, the fermentation observed can also be associated with CGF, since corn fibre presents in vitro fermentability (GUEVARA et al, 2008).…”
Section: Item ---------------------------------Inclusion Of Cgf (G Kgmentioning
confidence: 99%
“…A comprehensive review of technologies that may be used to assess the digestibility of foods for dogs and cats has recently been published by de Godoy et al (2016). Methods based on the use of digestibility markers (inert and indigestible dietary components), included at low concentrations in the diet, are widely used [for example, chromic oxide (Guevara et al 2008;Barry et al 2009), yttrium oxide (Vhile et al 2007) and celite (Scott & Boldaji 1997)]. Nowadays, the use of dogs as experimental animals is a source of great concern for most pet owners and many pet food producers would like to see a reduction in the need for in vivo trials with dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Burrows et al (28) reported that as the fiber in the diet increases, the time spent in the intestinal passage lengthens, and digestibility decreases. Fiber digestibility in dog food can be as low as 18%-31% (29). Fiber digestion was also low (45% and 35% for rice and barley, respectively) in the present study.…”
Section: Discussionmentioning
confidence: 68%